Daratumumab and its use in the treatment of relapsed and/or refractory multiple myeloma. (23rd August 2018) - Chehab, Sarah; Panjic, Elyse Hall; Gleason, Charise; Lonial, Sagar; Nooka, Ajay K
Daratumumab gained initial US FDA approval as fourth-line therapy among relapsed and/or refractory multiple myeloma (RRMM) patients who have received at least three prior lines of therapy, including a proteasome inhibitor (PI) and immunomodulatory drug (IMiD), or who are double refractory to a PI and an IMiD. Further combination trials of daratumumab led to FDA approvals in combination with bortezomib and dexamethasone or lenalidomide and dexamethasone for multiple myeloma patients who have received at least one prior therapy. The most recent expansion of the FDA approval of daratumumab comes in combination with pomalidomide and dexamethasone for patients with multiple myeloma that have received ≥2 prior lines of therapy including lenalidomide and a PI. The current manuscript reviews data supporting the efficacy and safety of daratumumab in RRMM.